The diverse roles of macrophages in metabolic inflammation and its resolution - Guha Ray, Aleepta; Odum, Oluwatomilayo Patience; Wiseman, Destini; Weinstock, Ada (Frontiers in Cell and Developmental Biology, 2023)
Macrophages are one of the most functionally diverse immune cells, indispensable to maintain tissue integrity and metabolic health. Macrophages perform a myriad of functions ranging from promoting inflammation, through inflammation resolution to restoring and maintaining tissue homeostasis. Metabolic diseases encompass a growing list of diseases which develop from a mix of genetics and environmental cues leading to metabolic dysregulation and subsequent inflammation. In this review, we summarize the contributions of macrophages to four metabolic conditions–insulin resistance and adipose tissue inflammation, atherosclerosis, non-alcoholic fatty liver disease and neurodegeneration. The role of macrophages is complex, yet they hold great promise as potential therapies to address these growing health concerns.